Negative electrode and battery

CN122996516APending Publication Date: 2026-10-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580023450.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-19
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0019]根据本公开的技术,对于包含碳纳米管的负极,能够在维持良好的电池特性的同时减少碳纳米管的量,进而还能够将用于形成采用通常方法制备得到的负极的浆料的粘度上升抑制得较小。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996516A_ABST
    Figure CN122996516A_ABST
Patent Text Reader

Abstract

The negative electrode (10) of the present disclosure includes a negative electrode mixture layer (11) containing a negative electrode active material and a conductive aid. The negative electrode active material includes: first active material particles containing a carbon material as a main component, and second active material particles containing silicon. The conductive aid includes carbon nanotubes and carbon black. The average fiber diameter of the carbon nanotubes is 0.5 nm or more and 6 nm or less, and the average fiber length is 1.2 μm or more and 8 μm or less. The mass ratio of the carbon black with respect to the carbon nanotubes is 10 or more and less than 40.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a negative electrode and a battery. Background Technology

[0002] In recent years, lithium-ion batteries and other rechargeable batteries have been widely used in applications requiring high capacity, such as automotive and energy storage. The electrodes that make up such batteries have a significant impact on their performance. Therefore, various studies have been conducted on electrodes in the past.

[0003] For secondary batteries such as lithium-ion batteries, high capacity is required. Therefore, the utilization of silicon (Si)-containing materials, as negative electrode active materials with high theoretical capacity density, has attracted much attention. In addition, to achieve high battery capacity, the current-collecting properties of the electrodes during charging and discharging, i.e., the conductivity of the electrodes, are also important.

[0004] For example, Patent Document 1 discloses a conductive composite comprising silicon-containing inorganic compound particles that function as a negative electrode active material and a conductivity-imparting agent that functions as a carbon nanotube aggregate. Patent Document 1 proposes using this conductive composite as the negative electrode of a lithium-ion secondary battery.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 2011-76948 Summary of the Invention

[0008] The problem the invention aims to solve

[0009] As described above, Patent Document 1 proposes a conductive composite comprising a silicon-containing anode active material and a conductivity-imparting agent for a carbon nanotube aggregate, which serves as the negative electrode. In this conductive composite, the conductivity-imparting agent, i.e., the carbon nanotube aggregate, is present in a proportion of up to 0.1% to 20% by weight. As a result, conventional anodes containing carbon nanotubes contain a large amount of carbon nanotubes.

[0010] Furthermore, to achieve higher capacity, research is underway to further increase the amount of silicon-containing anode active material. Since silicon-containing anode active materials exhibit significant volume changes during charge and discharge, increasing the amount of such active material necessitates increasing the amount of carbon nanotubes to maintain the current-collecting performance of the anode. However, when forming the anode using conventional methods—combining various constituent materials in a dispersion medium to form a slurry and then coating it—increasing the amount of carbon nanotubes to ensure sufficient current-collecting performance results in a highly viscous slurry, making homogeneous coating difficult and hindering the achievement of a good coating film. Additionally, carbon nanotubes are relatively expensive, increasing manufacturing costs. On the other hand, carbon nanotubes offer excellent current-collecting performance; therefore, reducing their amount makes it difficult to obtain good battery characteristics. It should be noted that the anode with a high proportion of carbon nanotubes disclosed in Patent Document 1 is manufactured using a special and complex method: first, a composite is formed by covering the surface of active material particles with an aggregate of carbon nanotubes, and then a slurry is prepared.

[0011] This disclosure provides the following technology: for anodes containing carbon nanotubes, it is possible to reduce the amount of carbon nanotubes while maintaining good battery characteristics, and further, it is possible to suppress the viscosity rise of the slurry used to form the anode prepared by conventional methods.

[0012] Solution for solving the problem

[0013] The negative electrode disclosed herein comprises a negative electrode composite layer including a negative electrode active material and a conductive additive.

[0014] The negative electrode active material comprises: first active material particles containing carbon material as the main component, and second active material particles containing silicon.

[0015] The conductive additive comprises carbon nanotubes and carbon black.

[0016] The carbon nanotubes have an average fiber diameter of 0.5 nm or more and 6 nm or less, and an average fiber length of 1.2 μm or more and 8 μm or less.

[0017] The mass ratio of carbon black to carbon nanotubes is greater than 10 and less than 40.

[0018] The effects of the invention

[0019] According to the technology disclosed herein, for anodes containing carbon nanotubes, the amount of carbon nanotubes can be reduced while maintaining good battery characteristics, and the viscosity increase of the slurry used to form anodes prepared by conventional methods can be suppressed to a smaller extent. Attached Figure Description

[0020] Figure 1This is a cross-sectional view showing a simplified configuration of an example of the negative electrode in Embodiment 1.

[0021] Figure 2 This is a schematic longitudinal cross-sectional view illustrating an example of the battery of Embodiment 2. Detailed Implementation

[0022] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. The present disclosure is not limited to the following embodiments.

[0023] (Implementation Method 1)

[0024] Figure 1 This is a simplified cross-sectional view showing an example of the negative electrode configuration in Embodiment 1. (As shown...) Figure 1 As shown, the negative electrode 10 of Embodiment 1 includes a negative electrode additive layer 11. The negative electrode additive layer 11 contains a negative electrode active material and a conductive additive. The negative electrode 10 also includes, for example, a negative electrode current collector 12, on which the negative electrode additive layer 11 is disposed.

[0025] The aforementioned negative electrode active material comprises: first active material particles containing carbon material as the main component, and second active material particles containing silicon. The aforementioned conductive additive comprises carbon nanotubes and carbon black. The average fiber diameter of the aforementioned carbon nanotubes is 0.5 nm or more and 6 nm or less, and the average fiber length is 1.2 μm or more and 8 μm or less. In the negative electrode additive layer 11, the mass ratio of carbon black to carbon nanotubes (hereinafter referred to as the "CB / CNT ratio") is 10 or more and less than 40.

[0026] It should be noted that in this specification, active material particles containing carbon as the main component and also containing silicon are classified as second active material particles. That is, in this specification, active material particles containing silicon are second active material particles, while active material particles that do not contain silicon and are mainly composed of carbon are first active material particles.

[0027] In Embodiment 1, the negative electrode additive layer 11 of the negative electrode 10 contains carbon nanotubes and carbon black as conductive additives with a CB / CNT ratio of 10 or more and less than 40. In this way, by containing carbon black in a manner that is 10 times or more and less than 40 times the amount of carbon nanotubes, the negative electrode 10 of Embodiment 1 can reduce the amount of carbon nanotubes while maintaining good battery characteristics. The negative electrode additive layer 11 contains: first active material particles containing carbon material as the main component; and second active material particles containing silicon, which undergoes significant volume changes with charge and discharge. By satisfying the above-mentioned range for the CB / CNT ratio, the negative electrode 10 of Embodiment 1 can suppress poor current collection of the negative electrode active material due to volume changes caused by charge and discharge, even with a reduced amount of carbon nanotubes, thus achieving good capacity retention. Furthermore, by satisfying the above-mentioned range for the CB / CNT ratio, even when preparing a slurry for forming the negative electrode additive layer using conventional methods, the viscosity increase of the slurry can be minimized. Unless otherwise specified, slurry refers to slurry used to form the negative electrode, specifically the slurry used to form the negative electrode binder layer.

[0028] As described above, the negative electrode 10 of Embodiment 1 can reduce the amount of carbon nanotubes while maintaining good battery characteristics, and can also suppress the viscosity increase of the slurry prepared by conventional methods to a small extent.

[0029] To achieve better battery characteristics, the CB / CNT ratio can be 15 or higher, or 20 or higher. On the other hand, to further suppress the increase in slurry viscosity, the CB / CNT ratio can be 35 or lower, or 30 or lower.

[0030] To achieve better battery characteristics and further suppress the increase in slurry viscosity, for example, the CB / CNT ratio can be above 15 and below 35, or above 15 and below 30.

[0031] The following describes in detail the various components of the negative electrode 10 in Embodiment 1.

[0032] <Negative Electrode Mixture Layer>

[0033] [Conductive additives]

[0034] (Carbon nanotubes)

[0035] Carbon nanotubes are carbon fibers with nanometer-sized diameters and extremely high aspect ratios (the ratio of fiber length to fiber outer diameter). For carbon fibers with such large aspect ratios, the contact between active materials and between the active material and the current collector is not point contact, but rather linear contact. Highly conductive carbon fibers are interspersed between the active material particles, forming linear contact portions with the particles. Thus, highly conductive carbon nanotubes form linear conductive paths between active materials and between the active material and the current collector, and form linear contact portions with the current collector, thereby improving current collection performance.

[0036] As described above, the carbon nanotubes included as conductive additives in the negative electrode binder layer 11 have an average fiber length of 1.2 μm or more and 8 μm or less. The average fiber length of the carbon nanotubes is 1.2 μm or more. In this case, even when the volume of the negative electrode active material changes significantly due to charging and discharging, the carbon nanotubes can maintain linear contact with the carbon nanotube fibers while following the volume change, thus maintaining electrical connection with the negative electrode active material. If the average fiber length of the carbon nanotubes is 1.2 μm or more, poor current collection is significantly suppressed. The average fiber length can be 1.5 μm or more, or 2 μm or more. On the other hand, as the average fiber length of the carbon nanotubes increases, the carbon nanotubes tend to aggregate, easily leading to poor dispersion and increased viscosity of the slurry due to carbon nanotube aggregation during slurry preparation. Furthermore, the longer the average fiber length, the higher the content of carbon nanotubes in the negative electrode binder layer 11 while ensuring the necessary number of carbon nanotubes, making it difficult to achieve high capacity. To achieve high capacity and facilitate the fabrication of a slurry in which carbon nanotubes and the anode active material are dispersed together during the manufacturing of the anode material, and to suppress the increase in slurry viscosity, the average fiber length of the carbon nanotubes is set to be below 8 μm. The average fiber length can be below 6 μm or below 4 μm. If the average fiber length of the carbon nanotubes is below 4 μm, the aggregation of carbon nanotubes is suppressed, and a well-dispersed slurry is easily obtained.

[0037] The average fiber length of carbon nanotubes can be greater than 1.2 μm and less than 6 μm, greater than 1.2 μm and less than 4 μm, greater than 1.5 μm and less than 4 μm, or greater than 2 μm and less than 4 μm.

[0038] As described above, the carbon nanotubes included as conductive additives in the negative electrode mixture layer 11 have an average fiber diameter of 0.5 nm or more and 6 nm or less. From the viewpoint of ease of manufacture, an average fiber diameter of 0.5 nm or more for the carbon nanotubes is acceptable, and preferably 1 nm or more. On the other hand, the larger the average fiber diameter of the carbon nanotubes, the fewer carbon nanotubes are contained in the negative electrode mixture layer 11 while keeping the carbon nanotube content the same, making it more difficult to suppress poor current collection. To suppress poor current collection, it is only necessary to increase the carbon nanotube content, but the more carbon nanotubes are present in the slurry, the easier it is for the carbon nanotubes to aggregate in the slurry, the more difficult it is to disperse uniformly, and the more likely the viscosity of the slurry will increase. Therefore, when manufacturing the negative electrode mixture layer 11, in order to easily produce a slurry in which carbon nanotubes and negative electrode active material are dispersed together, and to suppress the increase of slurry viscosity, the average fiber diameter of the carbon nanotubes is set to 6 nm or less. By setting the average fiber diameter to 6 nm or less, a negative electrode mixture layer 11 that significantly suppresses poor current collection and is easy to manufacture can be obtained. The average fiber diameter of carbon nanotubes is preferably less than 4 nm, and more preferably less than 3 nm.

[0039] The average fiber diameter of carbon nanotubes can be greater than 1 nm and less than 6 nm, greater than 1 nm and less than 4 nm, or greater than 1 nm and less than 3 nm.

[0040] Here, the average fiber length of carbon nanotubes was determined by image analysis using a scanning electron microscope (SEM). For example, the average fiber length was calculated by arbitrarily selecting 100 carbon nanotubes, measuring their fiber lengths, and averaging them. Fiber length refers to the length when forming a straight line. Fiber diameter refers to the length in the direction perpendicular to the fiber length, and is the outer diameter of the carbon nanotube. It should be noted that carbon nanotubes are sometimes not single fibers but formed in bundles, a state known as a bundle; the average length in this bundle state can also be used as the fiber length of each individual carbon nanotube. The average fiber diameter of carbon nanotubes can be determined by image analysis using a transmission electron microscope (TEM). Furthermore, for carbon nanotubes with two or fewer layers in their wall structure, the average fiber diameter was determined by analyzing the Raman shift in the Raman spectrometer, which occurs between 150 and 300 cm⁻¹. -1 By analyzing the RBM (Radial Breathing Mode) within a certain range, its diameter can be estimated. The average fiber diameter can be calculated by arbitrarily selecting 100 carbon nanotubes, measuring their diameters, and averaging them.

[0041] Carbon nanotubes are ideally composed of single-wall carbon nanotubes. This allows for effective suppression of poor current collection with a small number of carbon nanotubes, resulting in better battery characteristics. It should be noted that carbon nanotubes with an average fiber diameter of less than 5 nm contain a large number of single-wall carbon nanotubes. The single-wall carbon nanotubes can constitute more than 50%, 80%, 90%, or even 100% of the total carbon nanotube mass.

[0042] It should be noted that as long as the average fiber diameter is below 6nm, carbon nanotubes can include both double-walled and multi-walled carbon nanotubes.

[0043] In the negative electrode additive layer 11, the content of carbon nanotubes relative to the overall negative electrode active material can be 0.01% by mass or more and less than 0.10% by mass. In the negative electrode of Embodiment 1, by including carbon nanotubes and carbon black in the negative electrode additive layer 11 with a CB / CNT ratio of 10 or more and less than 40, even if the content of carbon nanotubes relative to the overall negative electrode active material is as low as 0.01% by mass or more and less than 0.10% by mass, poor current collection can be suppressed and better battery characteristics can be achieved. In addition, since the content of carbon nanotubes relative to the overall negative electrode active material is less than 0.10% by mass, the increase in slurry viscosity can be further suppressed.

[0044] In the negative electrode mixture layer 11, the content of carbon nanotubes relative to the overall negative electrode active material can be 0.01% by mass or more and 0.06% by mass or less. Even if the content of carbon nanotubes relative to the overall negative electrode active material is further reduced to 0.06% by mass or less, the negative electrode of Embodiment 1 can suppress poor current collection and achieve better battery characteristics. In addition, by further reducing the content of carbon nanotubes relative to the overall negative electrode active material to less than 0.06% by mass, the increase in slurry viscosity can be further suppressed.

[0045] The content of carbon nanotubes relative to the overall negative electrode active material was determined by extracting only the negative electrode binder layer from a sample obtained from a discharged secondary battery. Specifically, the discharged secondary battery was first disassembled, and the negative electrode was removed. Next, the negative electrode was cleaned with an organic solvent, then vacuum dried, and finally, only the negative electrode binder layer was peeled off, thus obtaining the sample. The pulverized sample was dispersed in a dispersion medium such as water and / or alcohol, and centrifuged to separate the carbon nanotubes. Furthermore, by performing thermal analysis such as TG-DTA (Thermogravimetry-Differential Thermal Analysis) on the sample, the ratio of binder components (excluding the negative electrode active material) to conductive material components could be calculated. By performing micro Raman spectroscopy on the cross-section of the negative electrode binder layer 11, the carbon species such as carbon nanotubes and acetylene black could be identified, and their proportions could be calculated from the thermal analysis such as TG-DTA of the peeled sample.

[0046] (Carbon black)

[0047] Carbon black is included as a conductive additive in the negative electrode composite layer 11 in a manner that satisfies the above-mentioned CB / CNT ratio. Any known type of carbon black can be used; there are no particular limitations.

[0048] In the negative electrode additive layer 11, the carbon black content relative to the negative electrode active material can be 0.5% by mass or more and 2.5% by mass or less. This suppresses poor current collection, resulting in better battery characteristics, and further inhibits the increase in slurry viscosity.

[0049] In the negative electrode additive layer 11, the carbon black content relative to the negative electrode active material can be more than 0.5% by mass and less than 1.5% by mass. This allows for the suppression of poor current collection, resulting in better battery characteristics, and further suppresses the increase in slurry viscosity.

[0050] The carbon black content relative to the negative electrode active material can be determined by the following method. Only the negative electrode binder layer 11 is stripped from the negative electrode 10, and the resulting powder is subjected to TG-DTA analysis in a nitrogen atmosphere. Based on the results of prior measurements using only carbon black, the carbon black content is determined from the weight loss above 600°C.

[0051] [Negative Electrode Active Material]

[0052] (First active substance particles)

[0053] The first type of active material particles are active material particles containing carbon materials as the main component. Here, the main component refers to the component with the highest content by mass percentage.

[0054] The carbon material can be graphite. That is, the first active material particles can be mainly composed of graphite. Among carbon materials, graphite has excellent charge-discharge stability and low irreversible capacity, so it is preferred. It should be noted that graphite refers to materials with well-developed graphite-type crystal structure, usually referring to carbon materials with an average interplanar spacing d002 of (002) plane less than 0.340 nm as determined by X-ray diffraction.

[0055] Examples of graphite include natural graphite, synthetic graphite, and graphitized mesophase carbon particles. Known graphite used as a negative electrode active material can be used. The negative electrode active material may contain carbon materials other than graphite.

[0056] The first active material particles can also contain carbon materials other than graphite as the main component. Examples of carbon materials other than graphite include easily graphitized carbon (soft carbon) and difficult-to-graphitize carbon (hard carbon).

[0057] Carbon materials can be used alone or in combination of two or more.

[0058] The average particle size of the first active material particles can be, for example, 5 μm or more and 30 μm or less. For first active material particles with such an average particle size, the effect of suppressing poor current collection caused by the conductive additive containing carbon nanotubes and carbon black at the above-mentioned CB / CNT ratio is significant.

[0059] It should be noted that the average particle size of the first active material particles was determined by observing the cross-section of the negative electrode compound layer using SEM or TEM. Particle types were identified using micro-Raman spectroscopy, and the grain boundaries of each particle were determined from the cross-sectional photographs. The diameter of the circle with the area defined by the grain boundary was taken as the particle size. At least 100 particles were randomly selected, and the average particle size was calculated as the average particle size.

[0060] When determining the average particle size of the first active material particles before the formation of the negative electrode mixture layer 11, the median particle size (D50), which accumulates to 50% of the volume in the volume-based particle size distribution, can be used. The median particle size can be determined, for example, using a laser diffraction / scattering particle size distribution measuring device.

[0061] The proportion of the first active material particles in the negative electrode active material can be, for example, 40% by mass or more and 90% by mass or less. This can increase the battery capacity.

[0062] (Second active substance particles)

[0063] The second active material particles are silicon-containing particles (hereinafter referred to as "silicon-containing particles").

[0064] In this specification, silicon-containing particles refer to particles of materials containing Si. Examples of Si-containing materials include elemental Si, Si alloys, Si compounds (Si oxides, etc.), and Si-containing composite materials.

[0065] As silicon oxides, SiO can be cited as an example. x For example, X can be 0.5≤X<2, or it can be 0.5≤X<1.6 or 0.8≤X≤1.6.

[0066] Silicon-containing particles can be, for example, particles of a composite material containing Si (hereinafter referred to as "composite particles").

[0067] For example, the second active material particles (i.e., silicon-containing particles) may comprise composite particles containing a matrix containing at least one element selected from the group consisting of carbon and oxygen, and a silicon phase dispersed in the matrix. The matrix functions, for example, as an ion-conducting phase. By using such composite particles as the negative electrode active material, the battery capacity can be increased. On the other hand, silicon-containing particles exhibit large volume changes during lithium ion uptake and release, making them prone to poor current collection due to repeated charge-discharge cycles. If poor current collection occurs, the electrical connection between the silicon-containing particles and other negative electrode active materials or current collectors is severed, isolating the silicon-containing particles. Isolated particles cannot contribute to capacity, thus resulting in poor current collection and reduced capacity retention. However, the negative electrode additive layer 11 contains a conductive additive comprising carbon nanotubes and carbon black at the aforementioned CB / CNT ratio, thus effectively suppressing poor current collection and maintaining a higher capacity retention.

[0068] As a matrix containing at least one element selected from the group consisting of carbon and oxygen, i.e., an ion-conducting phase, at least one element selected from the group consisting of SiO2 phase, silicate phase and carbon phase can be used, for example.

[0069] As an example of silicon-containing particles, one can use a selection of particles containing the formula SiO2. X The particles are at least one of the following groups: a first particle of silicon oxide (represented by 0.5 ≤ X < 1.6), a second particle containing a lithium silicate phase and a silicon phase dispersed in the lithium silicate phase, and a third particle containing a carbon phase and a silicon phase dispersed in the carbon phase. By using silicon-containing particles as the second active material particles, the battery capacity can be increased. On the other hand, silicon-containing particles have large volume changes with the absorption and release of lithium ions, and are prone to poor current collection due to repeated charge and discharge. If poor current collection occurs, the electrical connection between the silicon-containing particles and other negative electrode active materials or current collectors is broken, and the silicon-containing particles are isolated. Isolated particles cannot contribute to capacity, so the result of poor current collection is a reduced capacity retention rate. However, the negative electrode additive layer 11 contains a conductive additive containing carbon nanotubes and carbon black in the above-mentioned CB / CNT ratio, so poor current collection is effectively suppressed, and a higher capacity retention rate can be maintained.

[0070] The silicon-containing particles may comprise a plurality of particles selected from the group consisting of a first particle, a second particle and a third particle. For example, the silicon-containing particles may be composed of two particles selected therefrom, or may include all three of these particles. Specifically, the silicon-containing particles may comprise the first particle and the second particle, may comprise the first particle and the third particle, or may comprise the second particle and the third particle. Alternatively, the silicon-containing particles may comprise all of the first particle, the second particle and the third particle.

[0071] (First Particle)

[0072] The first particle is a mixture formed by mixing SiO₂ and Si fine particles at a microscopic level. The first particle includes, for example, a compound represented by the formula SiO X silicon oxide represented by (0.5≤X<1.6). The first particle may include a silicon oxide particle and a carbon layer disposed around the silicon oxide particle.

[0073] (Second Particle)

[0074] The second particle includes a lithium silicate phase and silicon particles (silicon phase) dispersed in the lithium silicate phase. The lithium silicate phase may include a compound represented by the formula Li 2Z SiO (2+Z) lithium silicate represented by (0<Z<2), or may be composed of this lithium silicate. Z preferably satisfies the relationship 0<Z<1. 50 mass% or more (for example, 60 mass% or more) of the lithium silicate phase may be composed of lithium silicate satisfying 0<Z≤0.5.

[0075] The second particle may comprise at least one element Me dispersed in the lithium silicate phase. The at least one element Me is at least one element selected from the group consisting of rare earth elements and alkaline earth metal elements. Examples of the alkaline earth metal elements include Mg, Ca, Sr, Ba and the like.

[0076] The element Me may be dispersed in the lithium silicate phase in the form of a Me oxide. The Me oxide may include at least one selected from the group consisting of yttrium oxide, cerium oxide, calcium oxide and magnesium oxide. The lithium silicate phase may include zirconium oxide. Furthermore, the element Me may be dispersed in the zirconium oxide.

[0077] The amount of element Me contained in the second particle is independent of the state of element Me or the type of compound of element Me. The amount calculated assuming element Me forms a stoichiometric oxide (estimated amount of Me oxide) can be used as an indicator. The estimated amount of Me oxide relative to the total of the lithium silicate phase and the silicon phase can be in the range of 0.001% by mass or more and 1.0% by mass or less. By making the estimated amount of Me oxide 0.001% by mass or more, the effect of reducing the reaction area and improving the hardness of the lithium silicate phase is increased. On the other hand, by making the estimated amount of Me oxide 1.0% by mass or less, the reduction in initial capacity can be suppressed.

[0078] The lithium silicate phase may contain metal compounds such as metal oxides, metal carbides, metal nitrides, and metal borides. Preferred metal compounds are metal oxides and metal carbides. Preferably, at least one compound selected from the group consisting of zirconium oxide (ZrO2), alumina (Al2O3), zirconium carbide (ZrC), tungsten carbide (WC), and silicon carbide (SiC) is used. The amount of the metal compound other than element Me relative to the total amount of the lithium silicate phase and the silicon phase can be in the range of 0.005% by mass or more and 15% by mass, or 0.01% by mass or more and 10% by mass, or 0.01% by mass or more and 1% by mass. The amount of the metal compound is calculated by assuming the metal element forms a stoichiometric oxide, similar to the amount of element Me.

[0079] The crystallite size of the silicon phase dispersed within the lithium silicate phase is, for example, 10 nm or more. The silicon phase is a particulate phase of elemental silicon (Si). By setting the crystallite size of the silicon phase to 10 nm or more, the surface area of ​​the silicon phase can be kept small, thus reducing the likelihood of silicon phase degradation associated with irreversible capacity formation. The crystallite size of the silicon phase is calculated using the Scherrer formula based on the half-width of the diffraction peaks on the Si(111) plane of the X-ray diffraction (XRD) pattern belonging to the silicon phase.

[0080] The average particle size of the silicon phase in the second particle is, for example, less than 500 nm, less than 200 nm, or less than 50 nm before the first charge. After the first charge, the average particle size of the silicon phase is, for example, less than 400 nm or less than 100 nm. By miniaturizing the silicon phase, the volume change during charge and discharge is reduced, and the structural stability of the second particle is further improved. The average particle size of the silicon phase in the second particle can be determined using SEM or TEM images obtained from SEM or TEM observation of the cross-section of the second particle exposing the silicon phase. Specifically, the average particle size of the silicon phase is calculated by averaging the maximum diameter of 100 silicon phases arbitrarily selected from the cross-sectional SEM or TEM images of the second particle.

[0081] From the viewpoint of increasing capacity and improving cycling characteristics, the content of the silicon phase (elemental Si) in the second particle is, for example, in the range of 20% by mass or more and 95% by mass or less, or in the range of 35% by mass or more and 75% by mass or less. Within this range, the diffusion of lithium ions becomes better, and excellent loading characteristics are easily obtained. Furthermore, the surface area of ​​the silicon phase exposed but not covered by the lithium silicate phase is reduced, and side reactions between the non-aqueous electrolyte and the silicon phase are suppressed.

[0082] The second particle may contain a conductive material covering at least a portion of its surface. Lithium silicate phases lack electronic conductivity, thus the conductivity of the second particle is prone to decrease. By covering the surface with a conductive material, conductivity can be dramatically improved. The conductive layer is preferably thin enough not to substantially affect the average particle size of the second particle. For example, from the viewpoint of ensuring conductivity and lithium-ion diffusion, the thickness of the conductive layer can be 1 nm or more and 200 nm or less, or 5 nm or more and 100 nm or less. Examples of materials and methods for forming the conductive layer will be described later.

[0083] (Third particle)

[0084] The third particle comprises a carbon phase and a silicon phase dispersed within that carbon phase. The carbon phase of the third particle can be composed of amorphous carbon (i.e., non-crystalline carbon). Amorphous carbon can be hard carbon, soft carbon, or other types of carbon. Amorphous carbon (non-crystalline carbon) generally refers to carbon materials with an average interplanar spacing d002 of the (002) plane exceeding 0.34 nm as determined by X-ray diffraction. The carbon phase of the third particle is conductive. Therefore, even if pores are formed around the third particle, the junction between the third particle and its surroundings is easily maintained. As a result, capacity reduction due to repeated charge-discharge cycles is easily suppressed.

[0085] The silicon phase content in the third particle can be 30% by mass or more and 80% by mass or 40% by mass or more and 70% by mass. Within this range, sufficient high capacity of the negative electrode can be achieved, and the cycle characteristics can be easily improved.

[0086] The average particle size of the silicon phase in the third particle can be, for example, greater than 1 nm. Alternatively, the average particle size of this silicon phase can be less than 1000 nm, less than 500 nm, less than 200 nm, less than 100 nm, or less than 50 nm. The finer the silicon phase, the smaller the volume change of the third particle during charging and discharging, and the better the structural stability of the third particle. The average particle size of the silicon phase in the third particle can be determined using the same method as described above for the average particle size of the silicon phase in the second particle.

[0087] The composition and component content of the second and third particles can be analyzed using the method described in International Publication No. 2018 / 179969.

[0088] The content of each element in silicon-containing particles can be determined, for example, by inductively coupled plasma atomic emission spectrometry (ICP-AES). Specifically, the silicon-containing particles are dissolved in a heated acid solution, carbon in the solution residue is removed by filtration, and the filtrate is then analyzed by ICP-AES to determine the spectral intensity of each element. Next, a standard curve is constructed using commercially available standard solutions of each element, and the content of each element is calculated.

[0089] The second and third particles each possess a so-called island structure. The silicon phases (islands) in the second and third particles are dispersed within silicate and carbon phase matrices (seas), respectively, and are covered by ion-conducting phases (silicate and carbon phases). In the island structure, the contact between the silicon phase and the electrolyte is restricted, thus suppressing side reactions. Furthermore, the stress generated by the expansion and contraction of the silicon phase is mitigated by the ion-conducting matrix.

[0090] The average particle size of the second active material particles can be, for example, 3 μm or more and 15 μm or less. For second active material particles with such an average particle size, the suppression effect of poor current collection caused by the conductive additive containing carbon nanotubes and carbon black at the above-mentioned CB / CNT ratio is significant. It should be noted that the average particle size of the second active material particles can be determined by the same method as the average particle size of the first active material particles.

[0091] The proportion of the second active material particles in the negative electrode active material can be, for example, 10% by mass or more and 60% by mass or less. This can increase the battery capacity.

[0092] The proportion of the second active material particles in the negative electrode active material can be, for example, 30% by mass or more and 60% by mass or less. This can further increase the battery capacity.

[0093] (The manufacturing method of the first particle)

[0094] SiO as the first particle X For example, it can be manufactured by vapor deposition. Alternatively, SiO can be coated with carbon using the following methods. X Particles. First, SiO... X The particle size was adjusted by crushing and classifying the particles. Next, the surface of the resulting particles was coated with carbon using CVD under an argon atmosphere. Then, by crushing and classifying them, a material denoted as SiO2 was prepared. X The first particle. It should be noted that regarding the use of carbon to cover SiO... XThe particle method is not limited to the methods described above; various well-known methods can be used. Additionally, the carbon-coated SiO2 step can be omitted. X Particle processing.

[0095] (Method for manufacturing the second particle)

[0096] Next, an example of a method for manufacturing the second particle will be described in detail. The second particle can also be manufactured by methods other than those described below. The second particle can be manufactured by the method described in International Publication No. 2018 / 179969.

[0097] The second particle is synthesized through two processes: a pre-process to obtain lithium silicate and a post-process to obtain the second particle from lithium silicate and raw silicon. When element Me is added, it can be added to the raw material of lithium silicate in the pre-process, but to avoid affecting the synthesis of lithium silicate, it is preferable to add it in the post-process. More specifically, the method for manufacturing the second particle preferably includes the following steps: step (i), mixing silicon dioxide and a lithium compound, and calcining the resulting mixture to obtain lithium silicate; and step (ii), compounding lithium silicate and raw silicon (and, if necessary, element Me) to obtain a second particle containing a lithium silicate phase and a silicon phase dispersed within the lithium silicate phase.

[0098] (Process (i))

[0099] From formula: Li 2Z SiO 2+Z The Z-value of lithium silicate can be controlled by the atomic ratio of silicon to lithium in the mixture of silicon dioxide and lithium compounds: Li / Si. To synthesize high-quality lithium silicate with low alkali leaching, it is preferable to have a Li / Si ratio less than 1.

[0100] Lithium compounds can include lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. These can be used individually or in combination of two or more.

[0101] The mixture containing silicon dioxide and lithium compounds is preferably heated in air at a temperature of 400°C or higher and 1200°C or lower, preferably 800°C or higher and 1100°C or lower, to react the silicon dioxide with the lithium compounds.

[0102] (Process (ii))

[0103] Next, lithium silicate and raw silicon are composited. For example, the mixture of lithium silicate and raw silicon (which may also contain element Me) can be pulverized while being subjected to shear force. Coarse silicon particles with an average particle size of several μm or more and less than tens of μm are used as raw silicon. The final silicon phase is preferably controlled such that the crystallite size, calculated by the Scherrer formula from the half-width of the diffraction peaks attributable to the Si(111) plane of the XRD pattern, is 10 nm or more.

[0104] Materials containing element Me (Me) for feeding can include oxides, oxalates, nitrates, sulfates, halides, and carbonates of Me. Among these, Me oxides are preferred due to their stability and good ionic conductivity. More specifically, examples include CeO2, Sc2O3, Y2O3, Er2O3, Tm2O3, Yb2O3, and Lu2O3. Alternatively, compounds containing elements other than Me and oxygen, such as yttrium-stabilized zirconium oxide, can also be used. These can be used individually or in combination of two or more.

[0105] For example, lithium silicate and raw silicon (a compound with the desired element Me) can be mixed in a specified mass ratio, and the mixture can be micronized while stirring using a pulverizing device such as a ball mill. However, the compounding process is not limited to this. For example, silicon nanoparticles and lithium silicate nanoparticles (a compound with the desired element Me) can be synthesized without using a pulverizing device and then mixed together.

[0106] Next, the micronized mixture is heated and sintered in an inert atmosphere (e.g., argon, nitrogen, etc.) at a temperature of 450°C or higher but below 1000°C. At this time, sintering can be performed while applying pressure to the mixture using hot pressing or similar methods to produce a sintered body of the mixture. Lithium silicate is stable, for example, at temperatures above 450°C but below 1000°C and hardly reacts with silicon; therefore, even if a capacity reduction occurs, it is only slight. During sintering, the silicate softens and flows to fill the gaps between the silicon phases. As a result, a dense, blocky sintered body with a silicate phase as the sea and a silicon phase as the islands can be obtained.

[0107] Then, the sintered body is crushed into granules to form the second particles. At this point, by appropriately selecting the crushing conditions, it is possible to obtain second particles with an average particle size within the aforementioned range.

[0108] After step (ii), a step (iii) can be performed to cover at least a portion of the surface of the second particle with a conductive material to form a conductive layer. The conductive material is preferably electrochemically stable, and carbon material is preferred. As a method for covering the surface of the particulate material with carbon material, a CVD method using hydrocarbon gases such as acetylene or methane as raw materials can be used. Alternatively, a method can be used where coal tar pitch, petroleum tar pitch, phenolic resin, etc., are mixed with the second particle and then heated. Alternatively, carbon black can be deposited onto the surface of the second particle.

[0109] The second particle can also be cleaned with acid. For example, it can be cleaned with an acidic aqueous solution. By cleaning with acid, trace amounts of components such as Li₂SiO₃ that may be generated during the composite formation of raw silicon and lithium silicate can be dissolved and removed. As the acidic aqueous solution, aqueous solutions of inorganic acids such as hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, phosphoric acid, and carbonic acid, and aqueous solutions of organic acids such as citric acid and acetic acid can be used.

[0110] (The manufacturing method of the third particle)

[0111] As examples of methods for manufacturing the third particle, the first and second methods are described below. The third particle can also be manufactured by methods other than those described below.

[0112] In the first method, raw silicon is first mixed with a carbon source, and then pulverized and compounded using a grinding device such as a ball mill. Alternatively, an organic solvent can be added to the mixture for wet grinding. In this process, the raw silicon is micronized to form a silicon phase. The silicon phase is dispersed within the carbon source matrix.

[0113] As a carbon source, it can be water-soluble resins such as carboxymethyl cellulose (CMC), hydroxyethyl cellulose, polyacrylate, polyacrylamide, polyvinyl alcohol, polyethylene oxide, and polyvinylpyrrolidone, cellulose, sugars such as sucrose, petroleum asphalt, coal tar, and tar, without particular limitation.

[0114] As organic solvents, alcohols, ethers, fatty acids, alkanes, cycloalkanes, silicates, metal alkoxides, etc. can be used.

[0115] Next, the composite of the silicon phase and the carbon source is heated in an inert gas atmosphere (e.g., argon, nitrogen, etc.) to, for example, above 700°C and below 1200°C. This heating carbonizes the carbon source, generating amorphous carbon. Thus, a third particle is obtained, in which the silicon phase is dispersed within a carbon phase containing amorphous carbon.

[0116] In the second method, firstly, raw silicon and carbon materials are mixed, and then pulverized and compounded using a grinding device such as a ball mill. Alternatively, an organic solvent can be added to the mixture for wet grinding. In this process, the raw silicon is micronized to form a silicon phase. This silicon phase is dispersed within the matrix of the carbon material.

[0117] By compositing the raw material silicon with carbon material as described above, a third particle containing a silicon phase dispersed in a carbon phase of amorphous carbon is obtained. The third particle can then be heated in an inert gas atmosphere to, for example, above 700°C and below 1200°C.

[0118] [Adhesive]

[0119] The negative electrode binder layer 11 may also include a binder. The binder may, for example, comprise at least one fluorine-free polymer material selected from the group consisting of carboxymethyl cellulose (CMC) and its alkali metal salts, polyacrylic acid and its alkali metal salts, and copolymers containing butadiene units. Fluorine-containing polymers, such as polytetrafluoroethylene (PTFE), are relatively expensive compared to general fluorine-free materials. Furthermore, fluorine-containing polymers present challenges in terms of reduction resistance. When used as the negative electrode in lithium-ion batteries, due to the low reaction potential of the active material, fluorine-containing polymers are electrochemically reduced, leading to deterioration through decomposition reactions such as defluorination. By using fluorine-free polymer materials, it is possible to suppress the degradation of electrode performance caused by electrochemical reduction degradation at a lower cost.

[0120] <Negative current collector>

[0121] The negative current collector 12 can be a sheet or film made of metallic materials such as stainless steel, nickel, copper, or their alloys. The sheet or film can be porous or non-porous. Metal foil, metal mesh, etc., can be used as the sheet or film. Carbon materials such as carbon can be coated onto the surface of the negative current collector 12 as a conductive auxiliary material.

[0122] The thickness of the negative electrode current collector 12 is not particularly limited. From the perspective of balancing the strength and lightweight of the negative electrode 10, it can be, for example, 1 μm or more and 50 μm or less, or 5 μm or more and 20 μm or less.

[0123] <Method for manufacturing the negative electrode>

[0124] For example, a slurry is prepared by dispersing a negative electrode additive comprising first active material particles, second active material particles, carbon nanotubes with an average fiber diameter of 0.5 nm or more and 6 nm or less, an average fiber length of 1.2 μm or more and 8 μm or less, and carbon black in a dispersion medium. After coating this slurry onto the surface of the negative electrode current collector 12 to form a coating film, the coating film is dried, thereby forming a negative electrode additive layer 11. The composition of the slurry can be determined according to the composition of the negative electrode 10 for manufacturing purposes; for example, a binder can be further added.

[0125] In the prepared slurry, the aforementioned carbon nanotubes and carbon black are added to the slurry in such a way that the CB / CNT ratio is greater than or equal to 10 and less than 40.

[0126] (Implementation Method 2)

[0127] The battery in Embodiment 2 includes a positive electrode, a negative electrode, and an electrolyte. The negative electrode is the same as that in Embodiment 1. According to this configuration, the battery in Embodiment 2, for the negative electrode containing carbon nanotubes, can reduce the amount of carbon nanotubes while maintaining good battery characteristics (specifically, capacity retention), and further suppresses the viscosity increase of the slurry used to form the negative electrode prepared by conventional methods.

[0128] Figure 2 This is a schematic longitudinal cross-sectional view illustrating an example of the battery of Embodiment 2. The battery 100 is a cylindrical battery comprising a cylindrical battery casing, a wound electrode assembly 24, and an electrolyte (not shown). The electrode assembly 24 is housed within the battery casing and is in contact with the electrolyte.

[0129] The battery casing consists of a bottomed cylindrical metal container, namely the casing body 25, and a sealing body 26 that seals the opening of the casing body 25. A gasket 37 is disposed between the casing body 25 and the sealing body 26. The gasket 37 ensures the airtightness of the battery casing. Inside the casing body 25, insulating plates 27 and 28 are respectively disposed at both ends of the electrode assembly 24 in the winding axis direction of the electrode assembly 24.

[0130] The housing body 25, for example, has a stepped portion 31. The stepped portion 31 can be formed by partially stamping the side wall of the housing body 25 from the outside. The stepped portion 31 can also be formed in an annular shape along the circumference of an imaginary circle defined by the housing body 25 on the side wall of the housing body 25. In this case, the sealing body 26 is supported, for example, by the surface on the opening side of the stepped portion 31.

[0131] The sealing body 26 includes a partially open metal plate 32, a lower valve body 33, an insulating member 34, an upper valve body 35, and a cover 36. These components are stacked in this order within the sealing body 26. The sealing body 26 is installed at the opening of the housing body 25 such that the cover 36 is located outside the housing body 25, and the partially open metal plate 32 is located inside the housing body 25.

[0132] The components constituting the sealing body 26 are, for example, circular or ring-shaped. All of these components, except for the insulating component 34, are electrically connected to each other.

[0133] Electrode assembly 24 has a positive electrode 21, a separator 22, and a negative electrode 23. The positive electrode 21, separator 22, and negative electrode 23 are all strip-shaped. The width direction of the strip-shaped positive electrode 21 and negative electrode 23 is, for example, parallel to the winding axis of electrode assembly 24. The separator 22 is disposed between the positive electrode 21 and the negative electrode 23. The positive electrode 21 and negative electrode 23 are wound into a spiral shape with the separator 22 spaced between them.

[0134] When observing the cross-section of the battery 100 in a direction perpendicular to the winding axis of the electrode assembly 24, the positive electrode 21 and the negative electrode 23 are alternately stacked in the radial direction of an imaginary circle defined by the housing body 25, with spacers 22 between them.

[0135] The positive electrode 21 is electrically connected to the cover 36, which also serves as the positive terminal, via a positive electrode lead 29. One end of the positive electrode lead 29 is connected, for example, near the center of the positive electrode 21 along its length. The positive electrode lead 29 extends from the positive electrode 21 to the partially open metal plate 32 through a through hole formed in the insulating plate 27. The other end of the positive electrode lead 29 is, for example, soldered to the side of the electrode assembly 24 of the partially open metal plate 32.

[0136] The negative electrode 23 is electrically connected to the housing body 25, which also serves as the negative terminal, via a negative electrode lead 30. One end of the negative electrode lead 30 is connected, for example, to the end of the negative electrode 23 along its length. The other end of the negative electrode lead 30 is, for example, soldered to the inner bottom surface of the housing body 25.

[0137] The following is a detailed explanation of the components of battery 100.

[0138] The positive electrode 21 contains a material having the property of absorbing and releasing metal ions (e.g., lithium ions). The positive electrode 21 may, for example, contain a positive electrode active material. The positive electrode 21 may, for example, have a positive electrode current collector and a positive electrode flux layer loaded on the surface of the positive electrode current collector.

[0139] As the positive current collector, sheets or films made of metallic materials such as aluminum, stainless steel, titanium, and their alloys can be used. Aluminum and its alloys are inexpensive and easy to fabricate into thin films, making them suitable materials for positive current collectors. The sheets or films can be porous or non-porous. Metal foils, metal meshes, etc., can be used as sheets or films. Carbon materials such as carbon can be coated on the surface of the positive current collector as conductive auxiliary materials.

[0140] The positive electrode layer contains the positive electrode active material. This active material can be a material capable of absorbing and releasing metal ions (e.g., lithium ions). Examples of suitable positive electrode active materials include lithium-containing transition metal oxides, lithium-containing transition metal phosphates, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal oxysulfides, and transition metal oxynitrides. In particular, using lithium-containing transition metal oxides or lithium-containing transition metal phosphates as the positive electrode active material can reduce battery manufacturing costs and increase the average discharge voltage. Examples of lithium-containing transition metal oxides include lithium cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, and lithium nickel manganese oxide. Examples of lithium-containing transition metal phosphates include lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, and lithium nickel phosphate.

[0141] The positive electrode binder layer may also include a binder. The material described in Embodiment 1 as a binder that can be used in the negative electrode binder layer may also be used in the positive electrode binder layer.

[0142] The positive electrode mixture layer may also include a conductive additive. As a conductive additive, the material described in Embodiment 1 as a conductive additive that can be used in the negative electrode mixture layer may also be used in the positive electrode mixture layer.

[0143] The negative electrode 23 contains a material that has the property of absorbing and releasing metal ions (e.g., lithium ions). The negative electrode 23 is the negative electrode 10 of Embodiment 1.

[0144] The electrolyte used as the electrolyte may contain a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. The concentration of the lithium salt in the electrolyte may, for example, be 0.5 mol / L or more and 2 mol / L or less. By controlling the lithium salt concentration within the above range, an electrolyte with excellent ionic conductivity and moderate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.

[0145] As a non-aqueous solvent, cyclic carbonates, linear carbonates, cyclic ethers, linear ethers, nitriles, amides, etc., can be used. One of these solvents can be used, or two or more can be used in combination.

[0146] As lithium salts, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bisperfluoroethylsulfonylimide (LiN(SO2C2F5)2), LiAsF6, LiCF3SO3, and lithium difluoro(oxalate-containing)borate, etc., can be used. One of these electrolyte salts can be used, or two or more can be used in combination.

[0147] Typically, a separator is desired between the positive and negative electrodes. The separator 22 has high ion permeability and possesses moderate mechanical strength and insulation. Microporous membranes, woven fabrics, and nonwoven fabrics can be used as the separator 22. The material used for the separator 22 can be, for example, a polymer. The polymer can be, for example, polyolefins such as polypropylene and polyethylene.

[0148] In the battery of Embodiment 2, the electrolyte may, for example, be impregnated with a polymer that serves as a separator. That is, the battery of Embodiment 2 may have a structure that combines an electrolyte and a polymer.

[0149] The battery of Embodiment 2 may further include a solid electrolyte as the electrolyte. That is, the battery of this disclosure may have a hybrid structure that combines an electrolyte and a solid electrolyte. Examples of solid electrolyte materials are halide solid electrolytes, sulfide solid electrolytes, oxide solid electrolytes, or organic polymer solid electrolytes. In this disclosure, "halide solid electrolyte" refers to a solid electrolyte containing a halogen element as the main component of the anions. "Sulfide solid electrolyte" refers to a solid electrolyte containing sulfur as the main component of the anions. "Oxide solid electrolyte" refers to a solid electrolyte containing oxygen as the main component of the anions. The main component of the anions refers to the anion with the largest molar mass among all the anions constituting the solid electrolyte.

[0150] As an example of the battery structure in Embodiment 2, it is explained Figure 2 The illustrated configuration example shows a cylindrical non-aqueous electrolyte secondary battery consisting of a wound electrode assembly with the positive and negative electrodes separated by a separator and an electrolyte housed in an outer packaging. However, the battery disclosed herein is not limited to this configuration example. The battery of Embodiment 2 can be any shape, such as square, coin-shaped, button-shaped, or laminated. Furthermore, instead of the wound electrode assembly, other types of electrode assemblies, such as those formed by stacking the positive and negative electrodes separated by a separator, can be used in the battery of Embodiment 2.

[0151] (Other implementation methods)

[0152] (Postscript)

[0153] Based on the description of the above embodiments, the following technology is disclosed.

[0154] (Technology 1)

[0155] A negative electrode comprising a negative electrode compound layer containing a negative electrode active material and a conductive additive.

[0156] The negative electrode active material comprises first active material particles containing carbon material as the main component and second active material particles containing silicon.

[0157] The conductive additive comprises carbon nanotubes and carbon black.

[0158] The carbon nanotubes have an average fiber diameter of 0.5 nm or more and 6 nm or less, and an average fiber length of 1.2 μm or more and 8 μm or less.

[0159] The mass ratio of carbon black to carbon nanotubes is greater than 10 and less than 40.

[0160] According to this configuration, for anodes containing carbon nanotubes, the amount of carbon nanotubes can be reduced while maintaining good battery characteristics, and the viscosity increase of the slurry used to form anodes prepared by conventional methods can be suppressed to a smaller extent.

[0161] (Technology 2)

[0162] According to the negative electrode of technology 1, the carbon nanotube comprises a single layer of carbon nanotubes.

[0163] Therefore, poor current collection can be effectively suppressed with a small amount of carbon nanotubes, thus resulting in better battery characteristics.

[0164] (Technology 3)

[0165] According to the negative electrode of technique 1 or 2, the mass ratio of the carbon black to the carbon nanotube is 15 or more and 30 or less.

[0166] Based on this configuration, better battery characteristics can be achieved, and the viscosity increase of the slurry can be further suppressed.

[0167] (Technology 4)

[0168] According to any one of the techniques 1 to 3, in the negative electrode compound layer, the content of the carbon nanotubes is more than 0.01% by mass and less than 0.10% by mass relative to the negative electrode active material.

[0169] Based on this configuration, better battery characteristics can be achieved, and the viscosity increase of the slurry can be further suppressed.

[0170] (Technology 5)

[0171] According to the negative electrode of technology 4, the content of carbon nanotubes in the negative electrode compound layer is more than 0.01% by mass and less than 0.06% by mass relative to the negative electrode active material.

[0172] Based on this configuration, better battery characteristics can be achieved, and the viscosity increase of the slurry can be further suppressed.

[0173] (Technology 6)

[0174] According to any one of the techniques 1 to 5, in the negative electrode mixture layer, the content of carbon black is 0.5% by mass or more and 2.5% by mass or less relative to the negative electrode active material.

[0175] Based on this configuration, better battery characteristics can be achieved, and the viscosity increase of the slurry can be further suppressed.

[0176] (Technology 7)

[0177] According to the negative electrode of technology 6, the content of carbon black in the negative electrode mixture layer is more than 0.5% by mass and less than 1.5% by mass relative to the negative electrode active material.

[0178] Based on this configuration, better battery characteristics can be achieved, and the viscosity increase of the slurry can be further suppressed.

[0179] (Technology 8)

[0180] According to any one of techniques 1 to 7, the negative electrode, wherein the second active material particles comprise composite particles, the composite particles comprising: a matrix containing at least one element selected from the group consisting of carbon and oxygen, and a silicon phase dispersed in the matrix.

[0181] This configuration enables the achievement of better battery characteristics.

[0182] (Technology 9)

[0183] The negative electrode according to any one of techniques 1 to 8, wherein the average particle size of the second active material particles is 3 μm or more and 15 μm or less.

[0184] This configuration enables the achievement of better battery characteristics.

[0185] (Technology 10)

[0186] According to any one of the techniques 1 to 9, the negative electrode contains the second active material particles in the negative electrode active material at a content of 10% by mass or more and 60% by mass or less.

[0187] This configuration allows for an increase in battery capacity.

[0188] (Technology 11)

[0189] According to the negative electrode of technology 9, the content of the second active material particles in the negative electrode active material is more than 30% by mass and less than 60% by mass.

[0190] This configuration allows for an increase in battery capacity.

[0191] (Technology 12)

[0192] The negative electrode according to any one of techniques 1 to 11, wherein the first active material particles contain graphite as the main component.

[0193] This configuration allows for an increase in battery capacity.

[0194] (Technology 13)

[0195] According to any one of techniques 1 to 12, the negative electrode wherein the average particle size of the first active material particles is 5 μm or more and 30 μm or less.

[0196] This configuration allows for an increase in battery capacity.

[0197] (Technology 14)

[0198] The negative electrode according to any one of techniques 1 to 13, wherein,

[0199] The negative electrode mixture layer also includes a binder.

[0200] The adhesive comprises at least one fluorine-free polymer selected from the group consisting of carboxymethyl cellulose and its alkali metal salts, polyacrylic acid and its alkali metal salts, and copolymers containing butadiene units.

[0201] This configuration allows for an increase in battery capacity.

[0202] (Technology 15)

[0203] A battery that has the following features:

[0204] The negative electrode according to any one of claims 1 to 15;

[0205] Positive electrode; and

[0206] Electrolytes.

[0207] According to this configuration, for anodes containing carbon nanotubes, the amount of carbon nanotubes can be reduced while maintaining good battery characteristics, and the viscosity increase of the slurry used to form anodes prepared by conventional methods can be suppressed to a smaller extent.

[0208] Example

[0209] The present disclosure will now be described in more detail using examples. These examples are merely illustrative and are not intended to limit the scope of the disclosure.

[0210] <Making the Negative Electrode>

[0211] [Examples 1-6 and Comparative Examples 1-5]

[0212] A negative electrode slurry was prepared by mixing the negative electrode active material, sodium polyacrylate (PAA-Na), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), carbon nanotubes (CNTs), carbon black (CB) (SuperC65), and water at a specified mass ratio. Monolayer carbon nanotubes were used as the carbon nanotubes. The average fiber length of the monolayer carbon nanotubes used was 5 μm, and the average fiber diameter was 1.6 nm. The CB / CNT ratio in the negative electrode slurry is shown in Table 1. Graphite was used as the first active material particle, and silicon-containing particles were used as the second active material particle.

[0213] Next, a coating film is formed by applying a negative electrode mixture slurry to the surface of the copper foil (negative electrode current collector). After the coating film dries, it is calendered. In this way, negative electrode mixture layers are formed on both sides of the copper foil. When the negative electrode active material (total of graphite and silicon-containing particles) is set to 100% by mass, the content of carbon nanotubes and carbon black in the negative electrode mixture slurry is as shown in Table 1 by mass. The mixing ratio of negative electrode active material, sodium polyacrylate, sodium carboxymethyl cellulose, and styrene-butadiene rubber in the negative electrode slurry is set as negative electrode active material:PAA-Na:CMC-Na:SBR = 100:0.5:1:1 by mass. It should be noted that the mass ratio of graphite to silicon-containing particles in the negative electrode active material is graphite:silicon-containing particles = 50:50.

[0214] The silicon-containing particles used as the second active material particles are composite particles containing Si and C, i.e., the aforementioned third particles containing both carbon and silicon phases, which are prepared by the following method. The preparation of the third particles is as follows.

[0215] SiO2 nanoparticles modified with CTAB were prepared by mixing tetraethoxysilane (TEOS) and hexadecyltrimethylammonium bromide (CTAB) in a mixed solution of ethanol / water / ammonia. Resorcinol, formaldehyde, and a surfactant (Pluronic F-127) were added to induce polymerization, resulting in polymer particles containing the aforementioned SiO2 nanoparticles. The molar ratio of surfactant to resorcinol (surfactant / resorcinol) was set to 0.005, and the mass ratio of resorcinol to TEOS (resorcinol / TEOS) was set to approximately 0.5 / 1. After drying, the polymer particles were carbonized at 800°C under a nitrogen atmosphere, further mixed with magnesium powder, and heated at 650°C under an argon atmosphere to induce a magnesothermic reduction reaction. MgO was dissolved from the reacted particles using a mixed solution of HCl / H2O / ethanol, and the particles were washed with ethanol and dried, thereby producing mesoporous silicon-containing particles with an average particle size of 8 μm containing both Si and C. The silicon-containing particle was used as the third particle.

[0216] <The Making of the Positive Electrode>

[0217] LiNi is used as the positive electrode active material. 0.88 Co 0.09 Al 0.03 O2. A positive electrode slurry is prepared by mixing the positive electrode active material, acetylene black, polyvinylidene fluoride, and N-methyl-2-pyrrolidone (NMP) in a specified mass ratio. Next, the positive electrode slurry is coated onto the surface of an aluminum foil serving as the positive electrode current collector. After the coating dries, it is calendered to form a positive electrode additive layer on both sides of the aluminum foil.

[0218] <Preparation of Electrolyte>

[0219] An electrolyte was prepared by adding LiPF6 as a lithium salt to a mixed solvent containing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7. The concentration of LiPF6 in the non-aqueous electrolyte was 1.3 mol / L.

[0220] <Battery Making>

[0221] Lead tabs are attached to each electrode. Then, the positive and negative electrodes are wound into a spiral shape with the leads at the outermost periphery, separated by a separator. This forms the electrode assembly. Next, the electrode assembly is inserted into an outer packaging made of a laminated film with an aluminum foil barrier layer, and then vacuum dried. Next, a non-aqueous electrolyte is injected into the outer packaging, and the opening of the outer packaging is sealed. This yields a secondary battery.

[0222] <Evaluation>

[0223] (Battery capacity degradation rate)

[0224] After completion, each battery was placed in an environment of 25°C and charged at a constant current of 0.5 It until the voltage reached 4.2V. Then, it was charged at a constant voltage of 4.2V until the current reached 0.02 It. Then, it was discharged at a constant current of 1.0 It until the voltage reached 2.5V. Then, it was left to stand for 20 minutes. This operation (charge-discharge cycle) was repeated 100 times. The charge and discharge were performed at an environment of 25°C.

[0225] The discharge capacity at the initial discharge is set as C0. The discharge capacity after 50 and 100 cycles of the above charge-discharge cycle is measured and recorded as C50 and C100, respectively. The change in capacity retention rate for each cycle is derived from the following formula and evaluated as the degradation rate (%).

[0226] (Deterioration rate (%) = 100 × (C50 - C100) / (C0 × 50)

[0227] The capacity retention rate, i.e. the degradation rate, is shown in Table 1. It should be noted that Table 1 shows the ratio, i.e. the degradation rate, with the degradation rate of Comparative Example 1 (without carbon black) as the baseline (1.00).

[0228] (Viscosity of the negative electrode mixture slurry)

[0229] The viscosity of the negative electrode slurry prepared and after 1 day was determined using the following method. The results are shown in Table 1. The viscosity of the slurry was measured using a Type B viscometer at 25°C. It should be noted that Table 1 shows the ratios, i.e., the viscosity ratios of the slurry, based on the viscosity of the negative electrode slurry of Comparative Example 1 (without carbon black) as a reference (1.00).

[0230] According to the results shown in Table 1, the batteries of Examples 1-6, with a CB / CNT ratio of 10 or higher and less than 40, exhibited lower degradation rates and better battery characteristics compared to the battery of Comparative Example 1, which did not contain CB. Furthermore, in this case, the increase in slurry viscosity was also minimized. In contrast, the batteries of Comparative Examples 2-4, with a CB / CNT ratio of less than 10, had degradation rates equal to or higher than Comparative Example 1, and their battery characteristics could not be maintained. In addition, the battery of Comparative Example 5, with a CB / CNT ratio of 40 or higher, showed a large increase in slurry viscosity.

[0231] [Table 1]

[0232]

[0233] Hereinafter, using Reference Examples 1-7, the relationship between the carbon nanotube content (relative to the mass percentage of the negative electrode active material) and the viscosity of the negative electrode slurry was evaluated using monolayer carbon nanotubes. The negative electrode slurries prepared in Reference Examples 1-7, compared to the negative electrode slurry of Comparative Example 1 which did not contain carbon black, had a carbon nanotube content varying from 0.03% to 0.10% of the negative electrode active material. It should be noted that the viscosity of the slurry was measured using the same method as that used for the slurries in the Examples and Comparative Examples. However, unlike the Examples and Comparative Examples, the viscosity of the reference examples was measured immediately after preparation. The results are shown in Table 2. Table 2 shows the ratios, i.e., the viscosity ratios of the slurries, with the viscosity of the negative electrode slurry of Reference Example 5 as a baseline (1.00).

[0234] [Table 2]

[0235]

[0236] According to the results shown in Table 2, if the carbon nanotube content is as high as 0.10% by mass relative to the negative electrode active material, the viscosity of the slurry becomes relatively large. Therefore, it can be confirmed that the carbon nanotube content relative to the negative electrode active material should ideally be less than 0.10% by mass.

[0237] Hereinafter, based on Reference Examples 8-11, the differences in battery characteristics were evaluated using single-layer carbon nanotubes (SWCNTs) and multi-layer carbon nanotubes (MWCNTs) as carbon nanotubes. The same single-layer carbon nanotubes as those used in the Examples and Comparative Examples were used. The average fiber diameter of the multi-layer carbon nanotubes used was in the range of 9 nm to 10 nm. The batteries used in the evaluation were the same as those in Comparative Example 1, except that the content of carbon nanotubes relative to the negative electrode active material was changed as shown in Table 3. It should be noted that Table 3 shows the ratio, i.e., the degradation rate ratio, based on the degradation rate of Reference Example 8 (1.00). In addition, the viscosity of the negative electrode slurry was also evaluated.

[0238] [Table 3]

[0239]

[0240] As shown in Table 3, comparing the results of Reference Example 8 and Reference Example 9, it is evident that multilayer carbon nanotubes, at the same amount as single-layer carbon nanotubes, struggle to maintain good battery characteristics, necessitating an increase in content. However, increasing the amount to improve battery performance leads to an increase in slurry viscosity. Therefore, single-layer carbon nanotubes are preferred as the carbon nanotubes.

[0241] Industrial availability

[0242] The technology disclosed herein is useful for batteries such as lithium-ion secondary batteries.

Claims

1. A negative electrode comprising a negative electrode active material and a conductive additive layer, The negative electrode active material comprises: first active material particles containing carbon material as the main component, and second active material particles containing silicon. The conductive additive comprises carbon nanotubes and carbon black. The carbon nanotubes have an average fiber diameter of 0.5 nm or more and 6 nm or less, and an average fiber length of 1.2 μm or more and 8 μm or less. The mass ratio of carbon black to carbon nanotubes is greater than 10 and less than 40.

2. The negative electrode according to claim 1, wherein, The carbon nanotubes comprise a single layer of carbon nanotubes.

3. The negative electrode according to claim 1, wherein, The mass ratio of carbon black to carbon nanotubes is 15 or more and 30 or less.

4. The negative electrode according to claim 1, wherein, In the negative electrode compound layer, the content of the carbon nanotubes is more than 0.01% by mass and less than 0.10% by mass relative to the negative electrode active material.

5. The negative electrode according to claim 4, wherein, In the negative electrode compound layer, the content of the carbon nanotubes is more than 0.01% by mass and less than 0.06% by mass relative to the negative electrode active material.

6. The negative electrode according to claim 1, wherein, In the negative electrode mixture layer, the content of carbon black is more than 0.5% by mass and less than 2.5% by mass relative to the negative electrode active material.

7. The negative electrode according to claim 6, wherein, In the negative electrode mixture layer, the content of carbon black is more than 0.5% by mass and less than 1.5% by mass relative to the negative electrode active material.

8. The negative electrode according to claim 1, wherein, The second active material particles comprise composite particles, the composite particles comprising: a matrix containing at least one element selected from the group consisting of carbon and oxygen, and a silicon phase dispersed in the matrix.

9. The negative electrode according to claim 1, wherein, The average particle size of the second active substance particles is greater than 3 μm and less than 15 μm.

10. The negative electrode according to claim 1, wherein, The content of the second active material particles in the negative electrode active material is more than 10% by mass and less than 60% by mass.

11. The negative electrode according to claim 10, wherein, The content of the second active material particles in the negative electrode active material is more than 30% by mass and less than 60% by mass.

12. The negative electrode according to claim 1, wherein, The first active substance particles contain graphite as the main component.

13. The negative electrode according to claim 1, wherein, The average particle size of the first active substance particles is greater than 5 μm and less than 30 μm.

14. The negative electrode according to claim 1, wherein, The negative electrode mixture layer also includes a binder. The adhesive comprises at least one fluorine-free polymer selected from the group consisting of carboxymethyl cellulose and its alkali metal salts, polyacrylic acid and its alkali metal salts, and copolymers containing butadiene units.

15. A battery comprising: The negative electrode according to any one of claims 1 to 14; Positive electrode; and Electrolytes.

Citation Information

Patent Citations

  • Conductive complex, and negative electrode for lithium ion battery

    JP2011076948A

  • Negative electrode material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    WO2018179969A1